Рефлексія як метод наукового осмислення культурних трансформацій - Копієвська, О.Р. (Культура народов Причерноморья, 2013)
The present article determines the role and importance of reflection in the knowledge of the cultural worldview, man’s self–knowledge, behavior and tastes on the basis of scientific society’s research. The article also examines the basic scientific approaches to the phenomenon of reflection as method of cultural transformations understanding on the factual material. By raising questions, concerning understanding the problems associated with the transition period in culture, the author defines reflection of the historical path and characterizes the flow process that is happening in the society now.